The impact of self-concept and its congruence with different brands on purchase intention: Evidence from Pakistani consumers - Moeed Ahmad Sandhu; Muhammad Usman; Zubair Ahmad; Muhammad Rizwan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Current research explores the effect of self-congruity (matching one.s self with brands) on brand attitude causing purchase intention. Mostly marketers communicate the conception that their brand matches with how ideally consumers want to see themselves. So, there is an imperious self-congruity effect applied to most brands universally. This research validates the previous theories of self-congruity in Pakistani context by confirming the positive consequence of self-congruity on brand-attitude and purchase intention. Current information is highly significant for segmentation as well as branding and promotional strategies. After initial data screening, statistics from 250 respondents was analyzed by using structural equation modeling (SEM, used here after) for verification of measurement as well as structural models. The results verified the theories of self-congruity and it is recommended that better targeting is required by understanding perceived self of the target market to be used in brand communication strategies. Findings of this study revealed that consumers evaluate brands by matching them with their perceived self (self-image) and accordingly develops attitude towards brands which ultimately influences their purchase intention i.e. those brands are preferred which matches with one.s perceived self-image. Findings also confirmed that Self-Congruity (the perception about one.s self) effects the consumer.s choice to prefer a particular brand (which matches to their perceived self) in the form of brand attitude which ultimately determines purchase intention. This understanding could be further used to improve segmentation and targeting decisions.
Keywords: 330; self-congruity; brand attitude; self-image; purchase intention; self-concept; Pakistani market